Compreensão sobre deficiência narrada por pessoas com cegueira adquirida na idade adulta - Matheus, Adrieli Camila Soares (Universidade Federal de São Carlos, 2021)
Currently there are several studies that describe disability from the biological, legislative, social and historical-cultural perspective; however, there are few who give voice to people with disabilities, talking about these people is more frequent than talking to them. For this reason, this study aimed to investigate the understanding of acquired blindness and the changes that occurred in the lives of people with blindness in adulthood. The study also reflected on the changes that occurred in their lives after vision loss and analyze the strategies used to overcome the challenges of being a person with acquired blindness. For this, he used the Life History method that allowed giving voice to people to whom he seeks to understand, no longer analyzing his disease/deviation, but sharing of their lives. It is a qualitative approach and a descriptive research, which portrayed reality and phenomena, from the perspective of people with acquired blindness, knowing the characteristics of this population. The study included four people with blindness acquired in adulthood, aged between 40 and 75 years, who attend a philanthropic institution, located in a city in the interior of the state of São Paulo. For data collection, unstructured interviews were used, which were recorded in audio and fully transcribed, in which the participants freely told about their stories. The data obtained were analyzed from discourse analysis. The results indicated that in relation to the understanding of acquired blindness, for the participants, the concepts are distinct and formed at different times, most often based on popular conceptions, without denying the medical conceptualization of disability; but above all they understand it from their social relationships, which are often watered down by discrimination, stereotypes, stigmas and social isolation. We conclude that this study contributed to the understanding of blindness, from the perspective of people with acquired blindness, being beneficial to these groups that are silenced and stigmatized
Understanding disability narrated by people with blindness acquired in adulthood
Keywords: Cegueira adquirida; Educação especial; História de vida; Compreensão da cegueira; Special education; Acquired blindness; Life story; Understanding blindness; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO